Experimental investigation on chloride-ion penetration resistance of slag containing fiber-reinforced concrete under drying-wetting cycles. (8th March 2021) - Chen, Weige; Zhu, Haitang; He, Zhenhao; Yang, Lin; Zhao, Liangping; Wen, Chengcheng
Highlights: The chloride profiles of various fiber-reinforced concrete were analyzed. The calculation method of D app under drying–wetting cycles condition was discussed. A quadratic function is proposed to describe the effect of slag content on D app . Small amount corrosion of steel fibers on the surface of concrete is beneficial. The favorable volume fraction of microfibers is less than 0.10 % . Abstract: The corrosion of reinforcing steel is a major problem of concrete structures, particularly those exposed to chloride environment. In this study, slag was incorporated as cement replacement in various types of fiber-reinforced concrete, and the chloride penetration resistance of the concrete was investigated. The specimens were exposed to drying-wetting conditions and the chloride ion content was determined via potentiometric titration. The results show that the apparent chloride diffusion coefficient decreases with an increase in exposure time, following an exponential relationship. Slag has a positive effect on the chloride penetration resistance of the concrete, and an optimal dosage of slag exists. The effect of macrofibers on the resistance of concrete to chloride ion penetration depends on the macrofiber material; steel fibers can improve the chloride ion penetration resistance of concrete, whereas macrofibers made of polypropylene exacerbate chloride ion penetration. The effects of microfibers are related to its type and volume fraction: A lower volume fraction is favorable, whereas a higher volume fraction weakens the resistance of concrete against chloride-ion penetration.